Wound care used topical ointment made from a combination of cherry leaf extract (Muntingia calabura L) and manuka honey on the healing process of superficial second-degree burns: a case report - Isnanti, Hervina; Wahyuningtyas, Eka Sakti; Handayani, Estrin; Wijayatri, Ratna (MEDISAINS, 2024)
Background: Burns are one of the most common accidental injuries in the community. Improper treatment of burns can lead to disability and even death. Applying topical therapy aims to reduce excessive collagen repositioning and accelerate healing. We tried treating burn wounds with an ointment that uses a combination of cherry leaf extract and manuka honey to test the effectiveness of wound healing.Case presentation: We report two cases of superficial burns that underwent wound treatment using an ointment containing cherry leaf extract and manuka honey.Conclusion: Wound treatment with an ointment containing cherry leaf extract and manuka honey can speed up the healing process in patients with superficial second-degree burns.